Visual Identity Components of Tourist Destination - Barišić, Petra (Array, 2014)
In the world of modern communications, visual identity has predominant influence on the overall success of tourist destinations, but despite of these, the problem of designing thriving tourist destination visual identity and their components are hardly addressed. This study highlights the importance of building and managing the visual identity of tourist destination, and based on the empirical study of well-known Medite rranean destinat ion of Croatia analyses three main components of tourist destination visual identity ; name, slogan, and logo. Moreover, the paper shows how respondents perceive each component of Croatia’s visual identity. According to study, logo is the most important, followed by the name and slogan. Research also reveals that Croatian economy lags behind developed countries in understanding the import ance of visual identity, and its influence on marketing goal achievements.